UPAYA KEPOLISIAN RESORT KOTA PAGAR ALAM DALAM MENANGGULANGI KEJAHATAN BEGAL DI MUSIM PACEKLIK DESA ALUN DUA TAHUN 2019 DITINJAU DARI HUKUM PIDANA ISLAM - Dhevira Nur Aisyah; Atika Atika; Fatah Hidayat (Universitas Islam Negeri Raden Fatah Palembang, 2021)
This thesis is entitled Pagar Alam City Police's Efforts to Overcome Begal Crime in the Badminton Season of Alun Dua Village 2019 in terms of Islamic Criminal Law. The method used in this study is empirical normative, with data collection techniques namely field and library research. get data in the form of primary data and secondary data from various kinds of references such as applicable laws and regulations, while empirical data is obtained from the Pagar Alam Police. The purpose of this study was to determine the number of cases of begging violence in Pagar Alam City in 2019, to find out how the efforts to deal with criminal acts of begging in the dry season were carried out by the City Police of Pagar Alam and to find out the view of Islamic criminal law on the efforts of Pagar Alam Police to overcome the crime of begging in the dry season, especially in the City of Pagar Alam. The results of the interview obtained from the Pidum section of the Pagar Alam Police regarding the police's efforts to tackle the crime of begging in Pagar Alam City, especially when in the dry season, often conduct joint patrols between the police and police at crime-prone points. During the long holiday, the Pagar Alam Police will anticipate by carrying out security at tourist attractions by placing members for several days at the tourist attraction, then on Saturday and Saturday nights there will be joint patrols led by the invisible or the head of the district. carry out raids at the prone points of these crimes. The obstacle from the police in overcoming this crime is that there are still many people who are not responsive in reporting 1X24 hours or do not immediately report to the local police, so that the perpetrators are far from reaching. Then the proceeds of crime or stolen goods have sometimes been directly sold to other areas as well as a wide network of the perpetrators of theft, making the investigation process difficult. Therefore it is necessary to cooperate with the community so that the perpetrators of these robberies are quickly caught. Key words: Robbery crime, police effort